2012
DOI: 10.1603/en12156
|View full text |Cite
|
Sign up to set email alerts
|

Constant Versus Fluctuating Temperatures in the Interactions Between <I>Plutella xylostella</I> (Lepidoptera: Plutellidae) and Its Larval Parasitoid <I>Diadegma insulare</I> (Hymenoptera: Ichneumonidae)

Abstract: Laboratory studies were conducted to determine the effects of constant temperatures (7, 22, and 30°C) and corresponding fluctuating temperatures (0-14, 15-29, and 23-37°C) on the development of diamondback moth, Plutella xylostella (L.), and its North American parasitoid Diadegma insulare (Hellén). Parasitized third-instar diamondback moth larvae were reared until adult mortality in individual thermal gradient cells at different temperature regimes. Larval mortality, parasitism success, pupal mortality, larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
52
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 27 publications
8
52
0
1
Order By: Relevance
“…However, thermoperiods can have profound effects on the development time of insects in comparison to constant temperatures (reviewed in Colinet et al, 2015), with an accelerating effect of fluctuating thermal regimes in many cases (Beck, 1983;Ratte, 1984;Fischer et al, 2011;Ragland & Kingsolver, 2008;Kingsolver et al, 2009;Radmacher & Strohm, 2011;Bahar et al, 2012;Kjaersgaard et al, 2013). In our study, we used a thermal fluctuation around a mean temperature of 20 °C, which is much colder than the optimal temperature for this species (around 13 25 °C) (Fleury et al, 2009;Moiroux et al, 2012), and thus is situated in the convex part of its performance curve.…”
Section: Development Timementioning
confidence: 99%
See 1 more Smart Citation
“…However, thermoperiods can have profound effects on the development time of insects in comparison to constant temperatures (reviewed in Colinet et al, 2015), with an accelerating effect of fluctuating thermal regimes in many cases (Beck, 1983;Ratte, 1984;Fischer et al, 2011;Ragland & Kingsolver, 2008;Kingsolver et al, 2009;Radmacher & Strohm, 2011;Bahar et al, 2012;Kjaersgaard et al, 2013). In our study, we used a thermal fluctuation around a mean temperature of 20 °C, which is much colder than the optimal temperature for this species (around 13 25 °C) (Fleury et al, 2009;Moiroux et al, 2012), and thus is situated in the convex part of its performance curve.…”
Section: Development Timementioning
confidence: 99%
“…Until now, very few studies considered the effects of daily thermal fluctuations on host-parasitoid relationships (Geden, 1997;Sigsgaard, 2000;Liu & Chen, 2001;Blanford et al, 2003;Mironidis & Savopoulo-Soultani, 2009;Reznik et al, 2009;Bahar et al, 2012;Bannerman & Roitberg, 2014) producing contrasting results. For example, Awadalla (1996) showed that temperature fluctuations during development led to a decrease in the success of the parasitoid Trissolcus megallocephalus on the green stink bug (Nezara viridula) compared to that observed in a constant thermal regime.…”
Section: Introductionmentioning
confidence: 99%
“…Golizadeh et al (2008) estimated the lower threshold temperature for another parasitic wasp of diamondback moth, Diadegma anurum (Thomson) (Hymenoptera: Ichneumonidae) to be 7.0ЊC. But there are no known reports of the thermal tolerance limits of the North American species, D. insulare, particularly in simultaneous studies with its host (Bahar et al 2012).…”
mentioning
confidence: 99%
“…There are a range of studies on thermal effects on diamondback moth (i.e., Liu et al 2002, Marchioro andFoerster 2011), and two studies on D. insulare (Bahar et al 2012. However, no study has covered the full range of temperatures suitable for the completion of the life cycles of diamondback moth or D. insulare.…”
mentioning
confidence: 99%
“…Further, Waite et al, (2000) introduced additional insects, that were previously reared at unspecified temperatures, into the experiment to supplement the numbers in treatments that had suffered high mortality. Introducing an insect to a modified rearing temperature will affect its development rate compared with insects reared under constant temperatures (Bahar et al 2012) and introduction of an insect that has already entered a given instar will incorrectly estimate the time that it typically takes to complete development through that instar at the new test temperature.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%